The dark corners of the night - Gardiner, Meg (Gardiner, Meg. UNSUB novel., 2020)
I am the legion of the night. He appears in the darkness like a ghost, made of shadows and fear- the Midnight Man. He comes for the parents but leaves the children alive, tiny witnesses to unspeakable horror. The bedroom communities of Los Angeles are gripped with dread, and the attacks are escalating. Still reeling from her best friend<U+2019>s close call in a bombing six months ago, FBI behavioral analyst Caitlin Hendrix has come to Los Angeles to assist in the Midnight Man investigation and do what she does best- hunt a serial killer. Her work is what keeps her going, but something about this UNSUB- unknown subject- doesn<U+2019>t sit right. She soon realizes that this case will test not only her skills but also her dedication, for within the heart of a killer lives a secret that mirrors Caitlin<U+2019>s own past. Hesitancy is not an option, but will she be able to do what must be done if the time comes?